A Review on State-of-the-Art Reviews in Wind-Turbine- and Wind-Farm-Related Topics - Manisha Sawant; Sameer Thakare; A. Prabhakara Rao; Andrés E. Feijóo-Lorenzo; Neeraj Dhanraj Bokde (Energies, 2021)
For decades of wind energy technology developments, much research on the subject has been carried out, and this has given rise to many works encompassing different topics related to it. As a logical consequence of such a research and editorial activity, state-of-the-art review works have also been published, reporting about a wide variety of research proposals. Review works are particularly interesting documents for researchers because they try to gather different research works on the same topic present their achievements to researchers. They act, in a way, as a guidance for researchers to quickly access the most meaningful works. The proposal of this paper consists of going one step further, and to present a review of state-of-the-art review works on wind-energy-related issues. A classification into several main topics in the field of energy research has been done, and review works that can be classified in all these areas have been searched, analyzed, and commented on throughout the paper.